Multifunctional rice cooker based on multistage temperature control - Guangzhou Haizhu (IJRDO - Journal of Electrical And Electronics Engineering, 2020)
a multifunctional rice cooker with multi-stage temperature control is introduced. Patent number: 200920052311.7(multistage temperature control electric rice cooker) Patent technical parameters measurement method.It has become China's strategic state policy to build an innovation-oriented country. Therefore, how to enhance the ability of independent innovation has become a major issue that has attracted high attention from all walks of life. In this paper, we discuss with readers the measurement method of the patent technical parameters of "a multifunctional rice cooker with multi-stage temperature control"patent number: ZL20052311.7. Through research and measurement and verification, product technical standards have been developed and applied to enhance independent innovation capabilities, thereby saving energy, reducing emissions of waste gas and improving the environment. Enhancing the core competitiveness of countries and enterprises to cope with the intense competition of globalization.